Intracardiac metastasis of squamous cell carcinoma of the penis - Sheila Aparecida Coelho Siqueira; Camila Satie Tomikawa (University of São Paulo, 2013)
Penile cancer shows variable incidence in different countries with a higher prevalence in developing countries. Squamous cell carcinoma represents the most common histologic type. The seventh decade of life corresponds to the mean age at diagnosis, but it is not an unusual diagnosis among young adults. Most cases present as "in situ" neoplasia or loco regional disease; however, systemic disseminated disease occurs via lymphatic and/or hematogeneous routes. The lymph nodes, liver, and lungs are the most frequently involved sites whereas the heart constitutes an exceptional and atypical site for penile cancer metastases. We report a case of a 79-year-old patient who presented a metastatic squamous cell carcinoma of the penis with intracardiac dissemination. The patient had a past history of cardiomyopathy, which required an artificial cardiac pacemaker implantation. He had been treated 1 year before with a partial penectomy but was admitted for emasculation due to the cancer relapse. During the postoperative period, he experienced sudden respiratory distress and died. The autopsy findings showed metastatic disease into the cardiac right chambers, pulmonary tumoral thrombi, and pulmonary hilar involvement. The authors call attention to the possibility of the presence of pacing leads, cardiomyopathy and the altered low blood flow in the right chambers, as predisposing factors for the tumoral seeding in this case.